Pursuing belonging through consumption: refining the belonging process framework - Vargas Bianchi, Lizardo (2022)
Purpose – Much research has been conducted on how consumption is related to human relationships. Only a scarcity of studies has examined brand and product selection, as well as the consumption activities that individuals follow when pursuing a sense of group belonging. The literature comprises a single theoretical framework describing this phenomenon, a nascent proposition on which further research remains undeveloped. This study aims to examine the transferability of that theoretical framework in a different context to that used for its elaboration and its descriptive scope on purchasing goods and engaging inn consumption activities to leverage belonging. Design/methodology/approach – A deductive qualitative case study and pattern matching analysis technique were used, followed by structural coding analysis of interview data. Findings – Findings reveal that the model is transferable, although its conceptual scope faces limitations. Individuals follow paths that need little or no excessive calculation in identifying a group to which they desire to belong, or the conduits to do so, and in certain cases the sense of belonging mediated by consumption is independent of display and confirmation by others. A refinement of the studied theoretical framework was carried out based on the findings, proposing an alternative framework termed the belonging-oriented consumption model, which provides a basis for future research on consumption related to pursuing a sense of belonging. Research limitations/implications – This study was limited to analysing those events in which consumption for the purpose of pursuing group belonging is intentional. However, much of our consumption happens in a nuanced and unreflective way, and the same must go for consumption related to belonging. Practical implications – The symbolic meaning that consumers attach to products and brands can vary based on how they are used and how consumers pursue a sense of belonging. The personality and distinctiveness of a product is influenced by the relationship between individuals and its use. Managers can establish concepts and elements of brand identity that ease brand display as a sign of belonging. They can also promote brand salience when the brand is used as a belonging conduit. Originality/value – This study is significant because there is limited development in the academic literature, nor agreement among the authors, of a model that describes the components of consumption oriented towards pursuing a sense of group belonging. The author proposes the belonging-oriented consumption model, which provides a theoretical basis for future research on this topic.